Work engagement and organizational commitment on millennial employees in terms of authentic leadership perception - Muhammad Hafiz; Indrayanti Indrayanti (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
Work engagement and organizational commitment are research concepts that still need to be studied in Indonesia. Millennial employees are the generation that is dominating almost all organizations in Indonesia. The study aimed to examine how the role of authentic leadership is on work engagement and organizational commitment for millennial employees. Data were collected from 171 millennial employees in private and start-up companies through online and offline surveys. The quantitative method by survey method was applied in this study. Three scales were used to collect data, including the Utrecht Work Engagement Scale of work engagement (17 items), Organizational Commitment Questionnaire (15 items), and Authentic Leadership Questionnaire (24 items). The data analysis used multivariate analysis of covariance (MANCOVA). Results showed authentic leadership has a positive role in work engagement and organizational commitment, so the research hypothesis is accepted. This study further clarifies the contribution of authentic leadership in generating high work engagement and organizational commitment of the millennial generation. By applying authentic leadership, the leader may enhance millennial employees' work engagement and organizational commitment.